The effect of DC bias and noise on the performances of power transformer - Syafruddin, Hasan
Direct current can be found in a transformer’s winding as a result of imperfections in connected equipment such as power electronics devices used and also due to magnetic disturbances of the earth’s field as geomagnetically induced currents (GIC). There are some host adverse effects that can potentially accompany the presence of direct current in a transformer’s windings, such as increased introducing extremely large voltage and current harmonic distortion, increased power losses, half-cycle saturated of the transformer core and elevated increasing of acoustic noise emission. This research involved the combination of MATLAB simulation and experimental works. Based on MATLAB program simulation, the results demonstrate that the exciting current becomes much more distort and will incline to half-circle saturation when the DC bias increases from 0.2 T to 1.0 T with the maximum saturation limit of AC magnetic flux density assumed as 2.0 T. A laboratory test is performed on lab-scale single phase power transformer. Excitation harmonics generated from dc biased and noise levels emitted by transformer core are investigated. The DC bias was injected simultaneously with AC source for no-load condition, meanwhile, through half wave rectifier with variable load for load situation. With DC bias, the transformer is prone to half-cycle saturated and rich harmonics are introduced. The simulated waveforms have good agreement with the measured one. The existence of DC bias was signified with zero and the significantly of even order harmonics beside of odd order harmonics. The harmonics contribute most to transformer noise. The higher magnetic flux density produces large harmonic and also higher noise such as 65.5, 68.4 and 72.4 dB for 1.3 T (under excited), 1.5 T (normal operation) and 1.9 T (over excited). The overall power losses and harmonics is lower for smaller core overlap length and thinner thickness of core lamination. The results of this study contribute in understanding transformers as harmonic and noise sources during DC bias existence.